THE OPTIMIZATION OF GRINDING DOSAGE ON GRINDING HARDENING - ZHANG NingJu; ZHAO MeiLin (Jixie qiangdu)
Aiming at the current situation of the grinding hardening test has certain blindness,the optimization design of the grinding process of grinding dosage was studied in depth and optimization of cutting parameter was proposed according to the grinding wheel topography. Taking specific grinding energy as the optimization goal,establishing the mathematical model with the chip surface roughness and the space as constraint condition,a complete model of the optimization of the grinding hardening was finally got. 40 Cr was taken as the research object,simplex method and graphical method were used to get the best combination of grinding dosage. In order to the correct evaluation of optimal dosage of grinding hardening effects,experimental verification was conducted and the materials were studied with the change of cutting depth. By measuring grinding force during tests,calculating specific grinding energy and heat source intensity from theoretical perspective; by testing vickers hardness and observing the microstructure of specimens from the perspective of the experimental research to study grinding hardening effect. The results showed that the optimized data is relatively reasonable and grinding hardening experiment under its guidance can reduce blindness and improve the effect of reinforcement.